On inverse topology problem for Laplace operators on graphs - Ershova, Yu.Yu.; Karpenko, I.I.; Kiselev, A.V. (Carpathian Mathematical Publications, 2014)
Laplacian operators on finite compact metric graphs are considered under the assumption that matching conditions at graph vertices are of δ type. Under one additional assumption, the inverse topology problem is treated. Using the apparatus of boundary triples, we generalize and extend existing results on necessary conditions of isospectrality of two Laplacians defined on different graphs. A result is also given covering the case of Schrodinger operators.